2020
DOI: 10.1007/s00018-019-03433-6
|View full text |Cite
|
Sign up to set email alerts
|

The cannabinoid ligands SR141716A and AM251 enhance human and mouse islet function via GPR55-independent signalling

Abstract: Aims Endocannabinoids are lipid mediators involved in the regulation of glucose homeostasis. They interact with the canonical cannabinoid receptors CB 1 and CB 2 , and it is now apparent that some cannabinoid receptor ligands are also agonists at GPR55. Thus, CB 1 antagonists such as SR141716A, also known as rimonabant, and AM251 act as GPR55 agonists in some cell types. The complex pharmacological properties of cannabinoids make it difficult to fully identify the relative importance of CB 1 and GPR55 in the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 69 publications
3
28
0
Order By: Relevance
“…This raises the possibility that GPR55 regulates glucose-stimulated insulin secretion. A recent study found no difference between wildtype and GPR55 knockout mice murine isolated islets of Langerhans in their responses to rimonabant ( Ruz-Maldonado et al, 2020 ), which is consistent with our finding that genotype did not affect the effect of rimonabant on et al glucose homeostasis. The authors did not discuss whether glucose-stimulated insulin secretion differed between islets from wild-type and knockout mice.…”
Section: Discussionsupporting
confidence: 93%
“…This raises the possibility that GPR55 regulates glucose-stimulated insulin secretion. A recent study found no difference between wildtype and GPR55 knockout mice murine isolated islets of Langerhans in their responses to rimonabant ( Ruz-Maldonado et al, 2020 ), which is consistent with our finding that genotype did not affect the effect of rimonabant on et al glucose homeostasis. The authors did not discuss whether glucose-stimulated insulin secretion differed between islets from wild-type and knockout mice.…”
Section: Discussionsupporting
confidence: 93%
“…As an additional complexity in facing ECS, it has to be taken into account that AM251 exhibits significant activity not only at CB 1 as an inverse agonist/antagonist, but also at orphan cannabinoid G-protein-coupled receptor 55 (GPR55) as an agonist [60][61][62][63]. The lack of homology between cannabinoid receptors may explain the differences among CB 1 and GPR55 in the signaling system and downstream cascade.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, the endocannabinoid system (ECS) is of particular interest since it was targeted by the cannabinoid (CB) receptor type 1 (CB 1 ) antagonist rimonabant to aid weight loss and improve glycaemic control [ 3 , 4 , 5 ]. The ECS is a cell-signaling network formed by endogenous ligands, named endocannabinoids, their enzymes of synthesis and degradation, and their receptors [ 6 , 7 , 8 , 9 ]. Phospholipid-derived endocannabinoids such as 2-arachidonoylglycerol and anandamide act as activators of the canonical CB 1 and CB 2 receptors [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Phospholipid-derived endocannabinoids such as 2-arachidonoylglycerol and anandamide act as activators of the canonical CB 1 and CB 2 receptors [ 6 ]. Both receptors belong to the seven-transmembrane G protein-coupled receptor (GPCR) conserved family and they are distributed centrally and peripherally in active metabolic tissues [ 6 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation